Concentration of Serum Biomarkers of Brain Injury in Neonates With a Low Cord pH With or Without Mild Hypoxic-Ischemic Encephalopathy - Gaulee, Pratima; Yang, Zhihui; Sura, Livia; Xu, Haiyan; Rossignol, Candace; Weiss, Michael D.; Bliznyuk, Nikolay (Frontiers in Neurology, 2022)
Objective To determine the concentrations of four neuroprotein biomarkers and 68 miRNAs in neonates with low cord pH and/or mild hypoxic-ischemic encephalopathy (HIE). Study Design A prospective cohort study enrolled neonates with low cord pH (n = 18), moderate-severe HIE (n = 40), and healthy controls (n = 38). Groups provided serum samples at 0–6 h of life. The concentrations of biomarkers and miRNAs were compared between cohorts. Result The low cord pH and moderate-severe HIE groups had increased concentrations of GFAP, NFL and Tau compared to controls (P < 0.05, P < 0.001, respectively). NFL concentrations in mild HIE was higher than controls (P < 0.05) but less than moderate-severe HIE (P < 0.001). Of 68 miRNAs, 36 in low cord pH group and 40 in moderate-severe HIE were upregulated compared to controls (P < 0.05). Five miRNAs in low cord pH group (P < 0.05) and 3 in moderate-severe HIE were downregulated compared to controls (P < 0.05). Conclusion A biomarker panel in neonates with low cord pH may help clinicians make real-time decisions.